Opportunities and Challenges of Implementing Communication Management in Organizations Managed by Gen-Z - Rumayanto, Tri; Sanusi, Siti Nurjannah; Bani, Sri Sutali (SAFE-Network, 2025)
Generational shifts in the workplace present new dynamics in organizational management, particularly in the communication aspect. This article discusses the implementation of communication management, along with the opportunities and challenges in organizations managed by Generation Z (Gen-Z). With Gen-Z's inherent affinity for digital technology, communication tends to be fast, flexible, and multi-channel. This opens up opportunities for efficient internal communication, increased collaboration, and innovation in conveying organizational messages. However, on the other hand, challenges arise, such as a low preference for formal communication, a generational gap with more senior team members, and the risk of miscommunication due to excessive use of digital media. This research uses a qualitative approach with a literature review. The analysis shows that successful communication management in this context is heavily influenced by cross-generational adaptability, digital literacy, and the development of an inclusive communication culture. These findings are expected to serve as a reference in designing more effective and sustainable organizational communication strategies in the era of new-generation leadership.